Transformation of the Labor Inspection System in Indonesia: Towards an Effective Centralized Model - Nasution, Faizal Amir P; Trisnantari, Sita Agung; Tobing, Henriko; Yuliastuti, Ari; Muhyiddin, Muhyiddin (Jurnal Ketenagakerjaan, 2024)
The labor inspection system in Indonesia plays a vital role in ensuring compliance with labor standards, protecting workers' rights, and creating a safe and productive work environment. However, its implementation faces numerous challenges, such as the limited number of labor inspectors, ineffective central-regional coordination, and minimal budget allocation. With an actual ratio of 1:57,000 formal workers—far below the ILO standard of 1:20,000—the labor inspection system remains suboptimal. This study aims to analyze the problems within the decentralized inspection system, evaluate the potential of a centralized inspection model, and formulate strategies and a roadmap for implementation. Using qualitative and quantitative approaches, including interviews, focus group discussions (FGD), and literature reviews, the study finds that a centralized labor inspection system is more effective in improving inspection standards, resource distribution, and cross-regional coordination. Benchmarking functional roles such as Family Planning Counselors and Mining Inspectors supports this recommendation. Implementation strategies include regulatory revisions, increasing the number of inspectors, improving competencies, and ensuring adequate budget provision through the national budget (APBN). A medium-term roadmap (2025–2029) has been developed to ensure a gradual and sustainable transition.